Rainfall Characteristics and Crop Production in Churu District of Western Rajasthan - Rao, A S; Purohit, R S; Mertia, R S (Annals of Arid Zone, 2016)
The rainfall characteristics, frequency of meteorological and agricultural drought, water-use yield relationships of pearl millet and kharif pulses of arid Churn District were studied. The meteorological droughts prevailed in 28 out of 10 I years (1906-2006) whereas, agricultural drought occurred in 18 out of 33 years (1971-2003). The actual evapotranspiration during reproductive stage of pearl millet and kharif pulses gave significant correlation with grain yields. Regression relationships of grain yield of pearl millet with rainfall explained 68% of the yield and with actual evapotranspiration 72-74%. Kharif pulses were less susceptible to drought than pearl millet attributed to difference in growth duration. Key words: Rainfall characteristics, weekly water balance, drought, pearl millet and kharif pulses, Churn District.